Fluid fluxing and accumulation drive decadal and short-lived explosive basaltic andesite eruptions preceded by limited volcanic unrest - Utami, Sri Budhi (2022)
Some volcanoes are known for repeatedly producing explosive but short-lived eruptions (half a day) every decade or so. These eruptions are often preceded by limited unrest signals and short run-up times to eruption (a few hours to months), and thus they are difficult to anticipate. Some well-documented examples are the 1990 and 2014 eruptions of Kelud volcano in Indonesia, or the 2015 Calbuco eruption in Chile. Here we interrogate the rock record and obtain insights into the processes and pre-eruptive conditions that led to the 1990 Kelud eruption, which we integrate with monitoring data (seismicity, lake temperature and hydro-Acoustics, sulfur emissions) towards a conceptual model for this type of events. Mineral-melt geothermobarometers indicate that the basaltic andesite magma carried a crystal cargo from as deep as 1519 km, and reached volatile saturation at 49 km with 24 wt.% water in the melt. The textures and compositional zoning of orthopyroxene and plagioclase do not support intrusion of more primitive magma as the driver for the eruption, and we instead propose that pre-eruptive fluid accumulation and hightemperature fluid fluxing from depth (likely dominated by CO2) played a major role in priming the eruption to occur. Such pre-eruptive gas accumulation is also supported by mass balance calculation of the emitted excess SO2 gas. Mg-Fe diffusion profiles in reversely zoned pyroxenes constrain timescales of weeks to months before eruption for fluid addition to the reservoir, and such events may be recorded in the monitoring signals, especially in the change of hydroacoustics and water lake temperature, and probably in the seismic swarms.We propose that fluid exsolution and accumulation in the shallow reservoir plays a crucial role in modulating and triggering short-lived explosive eruptions with brief unrest at Kelud and probably other volcanoes worldwide.